Add‐back therapy with GnRH analogues for uterine fibroids - Moroni, Rafael M (Cochrane Database Syst Rev, 2015)
BACKGROUND: Uterine fibroids (also known as leiomyomas) are the most common benign pelvic tumours among women. They may be asymptomatic, or may be associated with pelvic symptoms such as bleeding and pain. Medical treatment of this condition is limited and gonadotropin‐releasing hormone (GnRH) analogues are the most effective agents. Long‐term treatment with such agents, however, is restricted due to their adverse effects. The addition of other medications during treatment with GnRH analogues, a strategy known as add‐back therapy, may limit these side effects. There is concern, however, that add‐back therapy may also limit the efficacy of the GnRH analogues and that it may not be able to completely prevent their adverse effects. OBJECTIVES: To assess the short‐term (within 12 months) effectiveness and safety of add‐back therapy for women using GnRH analogues for uterine fibroids associated with excessive uterine bleeding, pelvic pain, or urinary symptoms. SEARCH METHODS: We searched electronic databases including the Cochrane Menstrual Disorders and Subfertility Group (MDSG) Specialised Register, CENTRAL, MEDLINE, PubMed, EMBASE, LILACS, CINAHL, PsycINFO; and electronic registries of ongoing trials including ClinicalTrials.gov, Current Controlled Trials, World Health Organization (WHO) International Clinical Trials Registry Platform. All searches were from database inception to 16 June 2014. SELECTION CRITERIA: Randomized controlled trials (RCTs) that included women with uterine fibroids experiencing irregular or intense uterine bleeding, cyclic or non‐cyclic pelvic pain, or urinary symptoms, and that compared treatment with a GnRH analogue plus add‐back therapy versus a GnRH analogue alone or combined with placebo were eligible for inclusion. DATA COLLECTION AND ANALYSIS: Two authors independently reviewed the identified titles and abstracts for potentially eligible records. Two review authors reviewed eligible studies and independently extracted data. Two authors independently assessed the studies' risk of bias. They assessed the quality of the evidence using GRADE criteria. MAIN RESULTS: Fourteen RCTs were included in the review. Data were extracted from 12 studies (622 women). The primary outcome was quality of life (QoL). Add‐back therapy with medroxyprogesterone (MPA): no studies reported QoL or uterine bleeding. There was no evidence of effect in relation to bone mass (standardized mean difference (SMD) 0.38, 95% confidence interval (CI) ‐0.62 to 1.38, 1 study, 16 women, P = 0.45, low quality evidence) and MPA was associated with a larger uterine volume (mean difference (MD) 342.19 cm(3), 95% CI 77.58 to 606.80, 2 studies, 32 women, I(2) = 0%, low quality evidence). Tibolone: this was associated with a higher QoL but the estimate was imprecise and the effect could be clinically insignificant, small or large (SMD 0.47, 95% CI 0.09 to 0.85, 1 study, 110 women, P = 0.02, low quality evidence). It was also associated with a decreased loss of bone mass, which could be insignificant, small or moderate (SMD 0.36, 95% CI 0.03 to 0.7, 3 studies, 160 women, I(2) = 7%, moderate quality evidence). Tibolone may, however, have been associated with larger uterine volumes (MD 23.89 cm(3), 95% CI= 8.13 to 39.66, 6 studies, 365 women, I(2) = 0%, moderate quality evidence) and more uterine bleeding (results were not combined but three studies demonstrated greater bleeding with tibolone while two other studies demonstrated no bleeding in either group). Four studies (268 women; not pooled owing to extreme heterogeneity) reported a large benefit on vasomotor symptoms in the tibolone group. Raloxifene: there was no evidence of an effect on QoL (SMD 0.11, 95% CI ‐0.57 to 0.34, 1 study, 74 women, P = 0.62, low quality evidence), while there was a beneficial impact on bone mass (SMD 1.01, 95% CI 0.57 to 1.45, 1 study, 91 women, P < 0.00001, low quality evidence). There was no clear evidence of effect on uterine volume (MD 27.1 cm(3), 95% CI ‐17.94 to 72.14, 1 study, 91 women, P = 0.24, low quality evidence), uterine bleeding or severity of vasomotor symptoms (MD 0.2 hot flushes/day, 95% CI ‐0.34 to 0.74, 1 study, 91 women, P = 0.46, low quality evidence). Estriol: no studies reported QoL, uterine size, uterine bleeding or vasomotor symptoms. Add‐back with estriol may have led to decreased loss of bone mass, from results of a single study (SMD 3.93, 95% CI 1.7 to 6.16, 1 study, 12 women, P = 0.0005, low quality evidence). Ipriflavone: no studies reported QoL, uterine size or uterine bleeding. Iproflavone was associated with decreased loss of bone mass in a single study (SMD 2.71, 95% CI 2.14 to 3.27, 1 study, 95 women, P < 0.00001, low quality evidence); there was no evidence of an effect on the rate of vasomotor symptoms (RR 0.67, 95% Cl 0.44 to 1.02, 1 study, 95 women, P = 0.06, low quality evidence). Conjugated estrogens: no studies reported QoL, uterine size, uterine bleeding or vasomotor symptoms. One study suggested that adding conjugated estrogens to GnRH analogues resulted in a larger decrease in uterine volume in the placebo group (MD 105.2 cm(3), 95% CI 27.65 to 182.75, 1 study, 27 women, P = 0.008, very low quality evidence). Nine of 12 studies were at high risk of bias in at least one domain, most commonly lack of blinding. All studies followed participants for a maximum of six months. This short‐term follow‐up is usually insufficient to observe any significant effect of the treatment on bone health (such as the occurrence of fractures), limiting the findings. AUTHORS' CONCLUSIONS: There was low or moderate quality evidence that tibolone, raloxifene, estriol and ipriflavone help to preserve bone density and that MPA and tibolone may reduce vasomotor symptoms. Larger uterine volume was an adverse effect associated with some add‐back therapies (MPA, tibolone and conjugated estrogens). For other comparisons, outcomes of interest were not reported or study findings were inconclusive.